(untitled) (Basel Institute on Governance Working Papers, 2023)
Este documento de trabajo analiza cuatro Pactos de Integridad en España implementados entre abril de 2017 y enero de 2019. Basándose en el análisis, ofrece recomendaciones específicas para medir y mejorar el impacto de los Pactos de Integridad, especialmente para lograr cambios a largo plazo. ***English*** Enhancing the impact of Integrity Pacts in public procurement: an analysis from Spain‘s experience This Working Paper analyses four Integrity Pacts in Spain implemented between April 2017 and January 2019. Based on the analysis, it offers specific recommendations to measure and enhance the impact of Integrity Pacts, especially in achieving long-term change.